PENERAPAN TEKNOLOGI FOTOVOLTAIK UNTUK PENERANGAN LINGKUNGAN DI SEKOLAH MENENGAH KEJURUAN MUHAMMADIYAH 2 TURI KABUPATEN SLEMAN - Muhammad Nadjib; Fitroh Anugrah Kusuma Yudha; Aditya Kurniawan (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
Muhammadiyah 2 Vocational High School in Turi, Sleman, Daerah Istimewa Yogyakarta, demonstrates a strong commitment to renewable energy, as shown by the presence of photovoltaic installations. However, these installations are still limited to supplying electricity for computer laboratories. The school frequently experiences power outages, particularly at night. To enhance safety and comfort during these periods, the school requires outdoor lighting that remains operational even when the PLN grid is down. This paper aims to apply photovoltaic technology to provide lighting for the school’s outdoor environment. The activities undertaken include designing and installing a photovoltaic system for the school terrace. The estimated daily load is determined based on the requirement of three LED lamps, each rated at 10 W. The system design consists of a solar module, a battery, and a charge controller. The final design specifies a 60 Wp solar module, a 70 Ah battery, and a controller with an 8 A input current. The solar module is installed on the tiled roof, while the battery, controller, timer, and panel box are placed indoors. The lamps are installed on the school terrace. The photovoltaic system operates effectively, providing illumination for four hours every night.